Розробка системи стежування за рухомими об’єктами - Гнилицький, Я. В. (ХНУРЕ, 2020)
The given work is devoted to the ability to track and store routes of moving objects. The modern level of technologies makes it possible to use navigation devices in the environment of mobile operators. In this work, compact trackers are used that perform the work of a terminal device of a mobile communication network based on the exchange of SMS messages. To be able to commit the routes of objects it is necessary to create application for the smartphone and connect the database to store related information. The task being solved is widely used in companies and everyday life to control cars, people and other objects